Inhibiting BDNF Signaling Upregulates Hippocampal H3K9me3 in a Manner Dependent On In Vitro Aging and Oxidative Stress - Ionescu-Tucker, Andra; Tong, Liqi; Berchtold, Nicole C.; Cotman, Carl W. (Frontiers in Aging, 2022)
Histone modifications are key contributors to the cognitive decline that occurs in aging and Alzheimer’s disease. Our lab has previously shown that elevated H3K9me3 in aged mice is correlated with synaptic loss, cognitive impairment and a reduction in brain derived neurotrophic factor (BDNF). However, the mechanism of H3K9me3 regulation remains poorly understood. In this study, we investigated the role of age-associated stressors on H3K9me3 regulation and examined if changes in H3K9me3 were age dependent. We used cultured hippocampal neurons at 6 days in vitro (DIV), 12 DIV and 21 DIV to examine the effect of different stressors on H3K9me3 across neuron ages. We found that the oxidative stressor hydrogen peroxide (H2O2) does not induce H3K9me3 in 12 DIV neurons. Inhibiting BDNF signaling via TrkB-Fc elevated H3K9me3 in 12 and 21 DIV neurons compared to 6 DIV neurons. Antioxidant treatment prevented H3K9me3 elevation in 12 DIV neurons treated with TrkB-Fc and H2O2. H2O2 elevated the epigenetic regulator SIRT1 in 6 DIV neurons but did not increase H3K9me3 levels. Our findings demonstrate that inhibiting BDNF signaling elevates hippocampal H3K9me3 in a manner dependent on in vitro age and oxidative stress.